The evaluation of cold tolerance of winter soft wheat sprouts according to a degree of root growth speed repair - A. V. Kalinina; S. V. Lyashcheva; A. D. Zavorotina; N. Yu. Larionova (Зерновое хозяйство России, 2018)
A.V. Kalinina, Candidate of Biological Sciences, leading research officer; S.V. Lyashcheva, Candidate of Agricultural Sciences, head of the breeding center; A.D. Zavorotina, senior research officer; N.Yu. Larionova, research officer FSBSI ‘Research Institute of Agriculture in South-East’ (410010, Saratov, Tulaykov Str., 7; tel.: 8(8452) 64-76-88; email: raiser_saratov@mail.ru, Kalininaal@mail.ru) The evaluation of cold tolerance of winter soft wheat sprouts according to a degree of root growth speed repair One of the most essential features of the assessment of winter crops tolerance to low temperatures is a level of repairing properties of a variety. The use of the sources of high adaptive properties as initial material is one of the most important terms of successful breeding of winter wheat. The article presents the results of the evaluation of cold tolerance of some varieties of winter soft wheat developed in Saratov and in other regions. The researches have been carried out by the laboratory of winter wheat breeding and seed-growing in Federal State Budgetary Scientific Institution ‘Research Institute of Agriculture in South-East’. The purpose of the study was to select the sources of high adaptive properties tolerant to low positive temperatures. As criteria for the assessment of the primary resistance and adaptive opportunities of the varieties, a degree of repairing growth speed of the main germinal root in per cents was used. The criteria can characterize not only primary tolerance and adaptive opportunities of the variety, but also its ability to homeostasis. Due to the conducted study, there have been found varietal differences of the tested parameter among the varieties belonging to various species of winter soft wheat (lutescens, suberythrospermum, gosteonum), as well as among the varieties belonging to single specie (lutescens). The varieties ‘Mironovskaya 808’, ‘Saratovskaya 8’, ‘Saratovskaya 90’, ‘Kalach 60’, ‘Sozvezdie’, ‘Saratovskaya 17’ and ‘Viktoriya 95’ have been found resistant and tolerant to low positive temperatures. The received data allow recommending these varieties as initial material for breeding of new varieties, hybrids and lines with this trait.